2017
DOI: 10.1007/s11010-017-3221-8
|View full text |Cite
|
Sign up to set email alerts
|

CLDN6 enhances chemoresistance to ADM via AF-6/ERKs pathway in TNBC cell line MDAMB231

Abstract: Claudin-6 (CLDN6), a critical tight junction protein acting as a tumor suppressor in breast cancer, is also considered to be a stem cell marker. Triple-negative breast cancer (TNBC) is a subtype of claudin-low and stem cell-like breast cancer which is chemoresistant to multiple anti-cancer drugs. The aim of our study was to determine whether CLDN6 plays a role in chemoresistance of TNBC. We found that overexpression of CLDN6 in TNBC cell line MDAMB231 significantly inhibited cell growth, migration, and invasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 37 publications
0
23
0
Order By: Relevance
“…Changes in CLDN gene expression were essentially seen in the CMS2 and CMS4 subtypes for which a clear distinction in sensitivity to chemotherapy-induced apoptosis has been reported 67. This suggests that in CRC, claudins could play a role in chemoresistance, as previously shown for CLDN4 and CLDN7 in ovarian cancer,68,69 and more recently, for CLDN6 in triple-negative breast cancer cells 70…”
Section: Discussionmentioning
confidence: 54%
“…Changes in CLDN gene expression were essentially seen in the CMS2 and CMS4 subtypes for which a clear distinction in sensitivity to chemotherapy-induced apoptosis has been reported 67. This suggests that in CRC, claudins could play a role in chemoresistance, as previously shown for CLDN4 and CLDN7 in ovarian cancer,68,69 and more recently, for CLDN6 in triple-negative breast cancer cells 70…”
Section: Discussionmentioning
confidence: 54%
“…Interestingly, Afadin has been demonstrated recently to interact with Claudin-6 in MDA-MB-231 breast cancer cells. Claudin-6 colocalized and interacted with Afadin, resulting in suppression of ERK signaling, increased stem cell characteristics, and enhanced chemoresistance to adriamycin (Yang et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Afadin has been shown to be important for heterotypic N-Cadherin/E-Cadherin interactions between cancer-associated fibroblasts and cancer cells that drive cellular invasion (Labernadie et al 2017). Afadin can also contribute to chemoresistance in TNBC cells through interactions with Claudin-6 and subsequent suppression of ERK signaling (Yang et al 2018). Roles for Afadin in modulating cell death and/or survival have also been reported.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, research has shown that estrogen receptor β (ERβ) plays an anti-cancer role in breast cancer, and Song et al demonstrated that this effect is mediated by claudin-6 [106]. On the other hand, Yang et al demonstrated that claudin-6 affects chemo-resistance in MDA-MB-231 cells in response to adriamycin (ADM) by reducing the drug-induced apoptosis [107]. Previous studies reported that decreased expression of claudin-2 is associated with increasing stage of cancer and with lymph node metastasis [108,109].…”
Section: Claudins In Breast Cancermentioning
confidence: 99%